Springtime in Burracombe - Harry, Lilian (London Orion Publishing Co., 2009)
The village of Burracombe is looking forward to the Coronation of Queen Elizabeth the Second, but the year of 1953 is to prove one of heartbreak as well as celebration. While Stella Simmons begins to plan her wedding to Felix Copley, her sister Maddy is only just coming to terms with the loss of her own fiance; Val and Luke Ferris are wondering if they will ever become parents, and Hilary Napier's chances of marriage seem first to come closer, then to recede. The Tozer family too face anxiety, as grandmother Minnie fights for her life, Tom and Joanna's premature twins battle with their own crisis and Jackie, working and living in Plymouth, is determined to live her own life. Meanwhile, the life of the village goes on, with all its ups and downs, its feuds and differences as bossy Joyce Warren tries to organise everything and everyone, Miss Kemp and Stella plan yet another event for the school, Jacob Prout strives to keep Burracombe looking its best for the festivities and, in the midst of it all, romance comes from a quite unexpected direction.
Keywords: Heading